The Utilization of Dehydroepiandrosterone as a Sexual Hormone Precursor in Premenopausal and Postmenopausal Women: An Overview - Justine Tang; Li-Ru Chen; Kuo-Hu Chen (MDPI AG, 2021)
Dehydroepiandrosterone (DHEA), and its metabolite, dehydroepiandrosterone sulfate ester (DHEAS), are the most abundant circulating steroid hormones, and are synthesized in the zona reticularis of the adrenal cortex, in the gonads, and in the brain. The precise physiological role of DHEA and DHEAS is not yet fully understood, but these steroid hormones can act as androgens, estrogens, and neurosteroids, and perform many roles in the human body. Since both levels decline with age, use of DHEA supplements have gained more attention due to being advertised as an antidote to aging in postmenopausal women, who may have concerns on age-related diseases and overall well-being. However, current research has not reached an overall consensus on the effects of DHEA on postmenopausal women. This overview is a summary of the current literature, addressing the metabolic pathway for DHEA synthesis and utilization, as well as the effects of DHEA on premenopausal and postmenopausal women with disease states and other factors. As for the therapeutic effects on menopausal syndrome and other age-related diseases, several studies have found that DHEA supplementations can alleviate vasomotor symptoms, preserve the integrity of the immune system, reduce bone loss, and increase muscle mass. Intravaginal DHEA has shown significant beneficial effects in menopausal women with severe vulvovaginal symptoms. On the other hand, DHEA supplements have not shown definitive effects in cardiovascular disease, adrenal insufficiency, insulin sensitivity, and cognition. Due to inadequate sample sizes and treatment durations of current studies, it is difficult to assess the safety and efficacy of DHEA and draw reliable conclusions for the physiological role, the optimal dosage, and the effects on premenopausal and postmenopausal women; therefore, the study of DHEA warrants future investigation. Further research into the roles of these steroid hormones may bring us closer to a therapeutic option in the future.